Individual and Combined Effects of Aflatoxin B1 and Sterigmatocystin on Lipid Peroxidation and Glutathione Redox System of Common Carp Liver - Benjamin Kövesi; Szabina Kulcsár; Zsolt Ancsin; Erika Zándoki; Márta Erdélyi; Miklós Mézes; Krisztián Balogh (Toxins, 2021)
The purpose of the study was to evaluate the short-term effects of aflatoxin B1 (AFB1 100 µg/kg feed) and sterigmatocystin (STC 1000 μg/kg feed) exposure individually and in combination (100 μg AFB1 + 1000 μg STC/kg feed) on the parameters of lipid peroxidation and glutathione redox system both in biochemical and gene expression levels in one-year-old common carp. Lipid peroxidation parameters were slightly affected, as significant differences were observed only in conjugated diene and triene concentrations. Reduced glutathione content decreased more markedly by STC than AFB1 or AFB1+STC, but glutathione peroxidase activity did not change. Expression of gpx4a, gpx4b, gss, and gsr genes was down-regulated due to STC compared to AFB1 or AFB1+STC, while an induction was found as effect of AFB1+STC in the case of gpx4a, but down-regulation for gpx4b as compared to AFB1. Expression of the glutathione biosynthesis regulatory gene, gss, was higher, but glutathione recycling enzyme encoding gene, gsr, was lower as an effect of AFB1+STC compared to AFB1. These results are supported by the changes in the expression of transcription factors encoding genes, nrf2, and keap1. The results revealed that individual effects of AFB1 and STC on different parameters are synergistic or antagonistic in multi-toxin treatment.